2020
DOI: 10.1021/acsmacrolett.9b00979
|View full text |Cite
|
Sign up to set email alerts
|

Vinyl Iodide Containing Polymers Directly Prepared via an Iodo-yne Polymerization

Abstract: Postpolymerization modifications are a prominent route for tuning polymer properties and diversifying materials. Thus, polymers containing robust chemical handles are desirable. Vinyl iodide functionality is commonly enlisted for selective transformations on small molecules, but these chemistries, while efficient enough for postpolymerization modifications, are less frequently performed on macromolecules due to limited methods to install vinyl iodide groups into polymers. Here, we present an iodo-yne polymeriz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Sletten et al put forward a novel iodo-yne polymerization assisted by sonication. 88 In this work, perfluorodiiodide in which iodide atoms were activated by electron-withdrawing fluorine groups could react with alkynes under the initiation of Na2S2O4, generating polymers with vinyl iodide functionality (Scheme 4c).…”
Section: Other Potential X-yne Click Polymerizationsmentioning
confidence: 97%
“…Sletten et al put forward a novel iodo-yne polymerization assisted by sonication. 88 In this work, perfluorodiiodide in which iodide atoms were activated by electron-withdrawing fluorine groups could react with alkynes under the initiation of Na2S2O4, generating polymers with vinyl iodide functionality (Scheme 4c).…”
Section: Other Potential X-yne Click Polymerizationsmentioning
confidence: 97%
“…[33][34][35][36] Previously, we had found that the reaction of fluorous vinyl iodides with phenols and catalytic copper under basic conditions gave a mixture of an Ullmann coupled vinyl ether and a fluorinated ene-yne. 37 Looking to better understand the mechanism of ene-yne formation and to establish the optimized conditions for this unique transformation, we built from the Ullmann conditions (Table 1, entry 1), employing vinyl iodide 5 as a model substrate and monitoring conversion by gas chromatography-mass spectrometry (GC-MS). The Ullmann conditions produced the desired ene-yne 6 in 55% yield, measured by integration of GC peaks.…”
Section: Special Topic Synthesismentioning
confidence: 99%
“…They also presented iodo-yne polymerization involving diynes and diiodoperfluoroalkanes to facilely obtain semifluorinated polymers with vinyl iodide groups throughout the polymer chains, which can be further modified via a variety of metal-catalyzed cross-coupling reactions. 26…”
Section: Introductionmentioning
confidence: 99%
“…They also presented iodo-yne polymerization involving diynes and diiodoperfluoroalkanes to facilely obtain semifluorinated polymers with vinyl iodide groups throughout the polymer chains, which can be further modified via a variety of metal-catalyzed cross-coupling reactions. 26 Stephenson and coworkers, 27 in 2012, reported an atom transfer radical addition reaction of different halides (bromine or iodine) and various types of olefins by redox quenching of photocatalysts to obtain a series of additive products of olefins and halides successfully. Inspired by this work, in 2017, our group developed a new effective method named step transferaddition and radical-termination (START) polymerization using transition metal photocatalysts under irradiation with blue LED light at room temperature to synthesize main-chaintype semifluorinated alternating copolymers by using both diiodoperfluoroalkanes and α,ω-unconjugated dienes as the monomers.…”
Section: Introductionmentioning
confidence: 99%